Prey composition of Peregrine Falcons (Falco peregrinus cassini) preying upon a mixed-species seabird colony in Argentine Patagonia - García, Germán Oscar (2014)
Predation is one of the main factors determining breeding strategies in many seabird species (Lack 1968, Burger & Gochfeld 1994, Gaston 2004). Among avian predators, raptors such as eagles, owls and falcons regularly prey on seabird adults and offspring (Paine et al. 1990, Holt 1994, Hayward et al. 2010). The Peregrine Falcon (Falco peregrinus) has a cosmopolitan distribution (White et al. 2002), and is regularly found along coastal areas of Argentine Patagonia which are characterized by large seabird breeding assemblages (Yorio et al. 1999). Peregrine Falcons from coastal populations in the Northern Hemisphere have been shown to be important predators of seabirds (Ratcliffe 1980, Paine et al. 1990, Velarde 1993), but very little is known on the contribution of seabird prey to Peregrine Falcon diet in coastal Argentina. Few studies have quantified their diet in Patagonia, and they indicate that prey composition may vary depending on location (Ellis et al. 2002, Santillán et al. 2010). Our goal was to determine the prey composition and contribution of seabirds to the diet of a pair of Peregrine Falcons breeding near a mixed-species seabird colony on the coast of Argentine Patagonia.